Number and type of vertebral deformities: epidemiological characteristics and relation to back pain and height loss. European Vertebral Osteoporosis Study Group. - Ismail, A; Cooper, C; Felsenberg, D; Varlow, J; Kanis, J; Silman, A; O'Neill, T (1999)
Vertebral deformity is the classical hallmark of osteoporosis. Three types of vertebral deformity are usually described: crush, wedge and biconcave deformities. However, there are few data concerning the descriptive epidemiology of the individual deformity types, and differences in their underlying pathogenesis and clinical impact remain uncertain. The aim of this study was to compare the epidemiological characteristics of the three types of vertebral deformity and to explore the relationships of the number and type of deformity with back pain and height loss. Age-stratified random samples of men and women aged 50 years and over were recruited from population registers in 30 European centers (EVOS study). Subjects were invited to attend for an interviewer-administered questionnaire and lateral spinal radiographs. The presence, type and number of vertebral deformities was determined using the McCloskey-Kanis algorithm. A total of 13,562 men and women were studied; mean age in men was 64.4 years (SD 8.5), and in women 63.8 years (SD 8.5 years). There was evidence of variation in the occurrence of wedge, crush and biconcave deformity by age, sex and vertebral level. Wedge deformities were the most frequent deformity and tended to cluster at the mid-thoracic and thoraco-lumbar regions of the spine in both men and women. Similar predilection for these sites was observed for crush and to a lesser extent biconcave deformities though this was much less marked than for wedge deformities. In both sexes the frequency of biconcave deformities was higher in the lumbar than the thoracic spine and unlike the other deformity types it did not decline in frequency at lower lumbar vertebral levels. The prevalence of all three types of vertebral deformity increased with age and was more marked in women. There were no important differences in the effect of age on the different deformity types. All types of deformity were associated with height loss, which was greatest for individuals with crush deformity. Back pain was also associated with all types of deformity. Overall, these results do not suggest important differences in pathophysiology between the three deformity types. Biomechanical factors appear to be important in determining their distribution within the spine. All deformity types are linked with adverse outcomes, though crush deformities showed greater height loss than the other deformity types.